Influence in art and literature. - Hermerén, Göran, 1938- (Princeton University Press, 1975)
This is a systematic study of the conceptual framework used by critics and scholars in their discussions of influence in art and literature. Göran Hermerén explores the key questions raised in scholarly debate on the topic: What is meant by "influence"? What methods can be used to settle disagreements about influence? What reasons could be used to support or reject statements about artistic and literary influence? The book is based on descriptive analyses in which the author has tried to make explicit what is said or implied in a number of "ations from scholarly writings on art and literature. Throughout, the emphasis is on clarifying the assumptions on which the use of the concept of influence is based, thus describing the limitations and merits of this kind of comparative research for critics and scholars.Originally published in 1975.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.